2017
DOI: 10.1016/j.bcp.2017.05.018
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA hsa-miR-370-3p suppresses the expression and induction of CYP2D6 by facilitating mRNA degradation

Abstract: Cytochrome P450 2D6 (CYP2D6) participates in the metabolism of approximately 20–25% of prescribed drugs. Genetic polymorphisms influence the expression and/or activity of CYP2D6, and inter-individual differences in drug activation and elimination caused by CYP2D6 genetic variants were reported. However, little is known about the potential modulation of CYP2D6 expression by microRNAs (miRNAs). In the current study, by using in silico prediction of the stabilities of miRNA/mRNA complexes, we screened 38 miRNA ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 39 publications
0
43
0
1
Order By: Relevance
“…Due to large interindividual variability in the expression of both TAP2 and miR‐1270, and the small human samples available for use in this study, the correlation between the expression of the T allele at TAP2 (rs241456) and miR‐1270 is not strong, but does indicate a trend of negativity. It is a common phenomenon that the correlations between miRNAs and their cognate mRNAs in human samples are possibly confounded due to the complexity of gene regulation and the diversity of genetic and environmental background among human populations(Yu et al, ; Jin et al, ; Chen et al, ; Wang et al, ; Zeng et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to large interindividual variability in the expression of both TAP2 and miR‐1270, and the small human samples available for use in this study, the correlation between the expression of the T allele at TAP2 (rs241456) and miR‐1270 is not strong, but does indicate a trend of negativity. It is a common phenomenon that the correlations between miRNAs and their cognate mRNAs in human samples are possibly confounded due to the complexity of gene regulation and the diversity of genetic and environmental background among human populations(Yu et al, ; Jin et al, ; Chen et al, ; Wang et al, ; Zeng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that miRNAs can modulate the expression of genes encoding drug metabolizing enzymes and transporters (Yu et al, ; Jin et al, ; Chen et al, ; Wang et al, ; Zeng et al, ). In this study, we hypothesized that a SNP in the 3′‐UTR of TAP2 interferes with miRNA binding, thus inhibiting the expression of the gene.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that miRNAs influence the expression of drug metabolizing enzymes (DMEs) (Jin et al 2016; Mohri et al 2010; Tsuchiya et al 2006; Wang et al 2017; Yu et al 2010, 2015a, b, c; Zeng et al 2017), which may thereby influence drug efficacy and safety (Koturbash et al 2015). miRNAs have been linked to liver injury and represent candidate biomarkers of liver injury because they are sufficiently stable in a wide range of biofluids, including serum (Baraniskin et al 2012; Chen et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Limitations of this study include (i) the lack of correction for multiple comparisons in the exploratory steps (for heuristic purposes to examine the potential predictors of CYP2D6 mRNA levels, before stepwise regression analysis), (ii) a relatively small sample size, and (iii) the focus on transcriptional regulators of CYP2D6 in investigating the determinants of CYP2D6 mRNA levels. Factors involved in post transcriptional regulation of CYP2D6 were not examined in this study, although microRNA hsa‐miR‐370‐3p was recently shown to bind to a coding region of CYP2D6 transcript and regulate CYP2D6 expression in liver cells . Due to the small sample size, the contribution of CYP2D6 SNPs of low allele frequency (accounting for ~ 70% of CYP2D6 SNPs identified in this study) to variable CYP2D6 mRNA levels was not examined in our liver tissue cohort.…”
Section: Discussionmentioning
confidence: 99%